Photocuring and digital light processing 3D printing of vitrimer composed of 2-hydroxy-2-phenoxypropyl acrylate and acrylated epoxidized soybean oil - Sigita Grauzeliene; Brigita Kazlauskaite; Edvinas Skliutas; Mangirdas Malinauskas; Jolita Ostrauskaite (eXPRESS Polymer Letters)
Vitrimers have gained attention as materials with recyclability, self-healing, and shape memory properties. The use of bio-based monomers for the synthesis of vitrimers is relevant because of the use of an environmentally friendly strategy. In this work, resins based on 2-hydroxy-2-phenoxypropyl acrylate and acrylated epoxidized soybean oil were designed and tested by real-time photorheometry, Fourier transform infrared spectroscopy (FT-IR), and mechanical testing to determine suitability for digital light processing 3D printing. The synthesis of vitrimer that could have good thermal properties and vitrimeric abilities, such as shape memory, self-healing, and recyclability properties, was investigated. Because of this, the vitrimer could repair cracks and defects and could have a complex design of several parts, which also contributes to recyclability and decreases costs. The rigidity and viscosity of the resins were reduced with an increasing amount of 2-hydroxy-2-phenoxypropyl acrylate-based monomer. The resin that has the highest amounts of hydroxyl and ester groups that are beneficial for transesterification reactions was chosen for vitrimer synthesis in order to show vitrimeric abilities such as self-healing, shape memory properties, reprocessability, and recyclability. The synthesized vitrimer was applied to digital light processing 3D printing and showed shape memory with a recovery ratio of 100%, self-healing and reprocessability with an efficiency of 47 and 31% and recyclability properties.